Comprehensive Radiolabeling, Stability, and Tissue Distribution Studies of Technetium-99m Single Amino Acid Chelates (SAAC) - Maresca, Kevin P; Hillier, Shawn M; Femia, Frank J; Zimmerman, Craig N; Levadala, Murali K; Banerjee, Sangeeta R; Hicks, Justin; Sundararajan, Chitra; Valliant, John; Zubieta, Jon; Eckelman, William C; Joyal, John L; et al. (Bioconjugate chemistry, 2009)
Technetium tricarbonyl chemistry has been a subject of interest in radiopharmaceutical development over the past decade. Despite the extensive work done on developing chelates for Tc(I), a rigorous investigation of the impact of changing donor groups and labeling conditions on radiochemical yields and/or distribution has been lacking. This information is crucially important if these platforms are going to be used to develop molecular imaging probes. Previous studies on the coordination chemistry of the {M(CO)3}+ core have established alkylamine, aromatic nitrogen heterocycles, and carboxylate donors as effective chelating ligands. These observations led to the design of tridentate ligands derived from the amino acid lysine. Such amino acid analogues provide a tridentate donor set for chelation to the metal and an amino acid functionality for conjugation to biomolecules. We recently developed a family of single amino acid chelates (SAAC) that serve this function and can be readily incorporated into peptides via solid-phase synthesis techniques. As part of these continuing studies, we report here on the radiolabeling with technetium-99m (99mTc) and stability of a series of SAAC analogues of lysine. The complexes studied include cationic, neutral, and anionic complexes. The results of tissue distribution studies with these novel complexes in normal rats demonstrate a range of distribution in kidney, liver, and intestines.